Are Technology-Enhanced Interventions Effective for Functional Improvements of Adults With Acquired Brain Injury?: A Systematic Review...American Occupational Therapy Association (AOTA) INSPIRE Annual Conference and Expo, April 3-5, 2025, Philadelphia, Pennsylvania. - Katz, Noga; Ransohoff-Brisson, Amy; Tarazona Sanchez, Katherine; Sicadsicad, Thurston Zane; Voelbel, Gerald (American Journal of Occupational Therapy)
Date Presented 04/04/2025 Technology is increasingly used in cognitive rehabilitation of adults with acquired brain injury (ABI), yet the effect on functional performance is unclear. The focus of this review supports the role of OT and evidence-informed practice. Primary Author and Speaker: Noga Katz Contributing Authors: Amy Ransohoff-Brisson, Katherine Tarazona Sanchez, Thurston Zane Sicadsicad, Gerald Voelbel